(untitled) (RevistAleph, 2018)
O estudo apresenta um relato de experiência decorrente da pesquisa qualitativa de doutorado/ Programa em Ensino em Biociências e Saúde/ IOC-Fiocruz. A pesquisa ocorreu na Fundação Municipal de Educação/Niterói - RJ. Teve por objetivo discutir os recursos de Comunicação Alternativa (CA) que viabilizam o acesso ao ensino de Ciências pelo discente com Deficiência Físico-Motora (DFM). O estudo foi realizado com três alunos DFM, envolvendo a formação de dois docentes de Sala de Recursos e a CA, na perspectiva inclusiva para o ensino de Ciências. A coleta de dados se realizou por meio de observação de campo do trabalho desses docentes e alunos, fotos e filmagens das intervenções pedagógicas e diário de campo. Resultados apontam a CA como um caminho para o ensino de Ciências de discentes DFM. The study presents an experience report from the qualitative research of PhD / Program in Teaching in Biosciences and Health / IOC-Fiocruz. The research was carried out at the Fundação Municipal de Educação / Niterói - RJ. The purpose of this study was to discuss the Alternative Communication (AC) resources that enable access to the teaching of Science by the student with Physical-Motor Deficiency (PMD). The study was carried out with three PMD students, involving the training of two Resource Room teachers and the AC, in an inclusive perspective for Science teaching. Data collection was carried out through field observation of the work of these teachers and students, photos and filming of pedagogical interventions and field diary. Results point to AC as a pathway to the science teaching of PMD students.